Effects of Ethanol Treatment on Storage Quality and Antioxidant System of Postharvest Papaya - Liu, Zhichao; Jiang, Fan; Mo, Yiming; Liao, Haida; Chen, Ping; Zhang, Hongna (Frontiers in Plant Science, 2022)
Papaya fruit is the fourth most favored tropical fruit in the global market, which has rich nutrition and can also be used for medicine and food processing. However, it will soften and mature in a short time after harvest, resulting in a lot of economic losses. In this study, we explored the effects of ethanol treatment on the storage quality and antioxidant system of papaya after harvest. The fruits were soaked in 0, 12.5, 25, 50 and 100 mL/L ethanol solutions for 2 h and stored at 25℃ for 14 d. It was found that ethanol treatment slowed the decline in fruit firmness, decreased the production of malondialdehyde (MDA), ethylene and superoxide anions, increased the activities of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), inhibited the activities of peroxidase (POD), phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO). In addition, principal component analysis (PCA) showed that PAL, ethylene, and superoxide anions were the main contributors for mature and senescence of postharvest papaya, which were the main components of PC1 (51.232%). In this experiment, ethanol treatment could delay ripening and senescence of papaya fruits, and 25 mL/L was the best concentration.